(3TQM GdhGajIs - (3GdCYQLj, GdMSjfj, eMeO Hf GdMSf Hf GdeQJVi, J (B1215(3g`s ((3Ydj Hf eMeO GdfLajs)
(3ChdgG (B:s
(3hMQeI GdXde hgPG GdeOdhd gh Mce gPGGdOdjd(B... (3bGd GdbSe GdChd ef GdCOdI GdYbdjI(B...s
(3BNQgG (B:s
(3eG Od Ydi UMI GdUdGI hhLhH eVi ajgG HCUd GdHQGAI(B... (3bO eQ aj GdeQLMGJ GdETGQI Edi eG jQLY Edi GdefUhU aGQLY Edj(B... (3hgh MSHfG hfYe Gdhcjd(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B237s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs